Comparative Effectiveness of Risankizumab vs Other Biologics in Crohn’s Disease: Long-Term and Quality-of-Life Outcomes after Inadequate Response to Prior Therapy - Babczyńska, Monika; Buliszak, Agnieszka; Marcjasz, Piotr; Bioły, Anna; Borończyk, Agnieszka; Zając, Piotr (Quality in Sport, 2025)
Introduction and Purpose: Crohn’s disease (CD) is a chronic inflammatory condition with an unpredictable course. Despite the availability of biologics, many patients fail to achieve sustained remission. Risankizumab, an anti-IL-23 p19 monoclonal antibody, offers a new therapeutic option. This study compares risankizumab with other biologics (infliximab, adalimumab, ustekinumab, vedolizumab), focusing on long-term outcomes and quality of life. Materials and Methods: This review analyzes data from phase III trials (ADVANCE, MOTIVATE, FORTIFY), the SEQUENCE head-to-head trial with ustekinumab, and observational studies. Outcomes assessed include clinical remission, endoscopic response, safety, and health-related quality of life (IBDQ, SF-36, FACIT-F). Brief Description of the State of Knowledge: Biologics targeting TNF-α, integrins, or IL-12/23 are effective but limited by non-response or loss of response. Risankizumab selectively inhibits IL-23, sparing the IL-12/Th1 pathway. It has demonstrated higher remission and mucosal healing rates than placebo and maintains efficacy in patients previously exposed to multiple biologics. Conclusions: Risankizumab is a safe and effective option in moderate-to-severe CD, especially after failure of other biologics. It improves both clinical and endoscopic outcomes, as well as patient quality of life. Further direct comparisons are warranted to clarify its role in treatment algorithms.